INSTITUTIONS OF SUPPORT FOR INNOVATIVE PRODUCTION ENTERPRISES - Ludmila TIMOTIN (Economica, 2016)
The article explores the specific forms of support for innovative entrepreneurship, including those oriented towards government cooperation,scientific research institutions and enterprises, in particular innovation vouchers, innovation incubators, clusters. The solution of the financial problems of the innovative business currently takes place through special institutions – venture capital funds, business angels.